Exposure of Reproductive-Aged Women to Multiple Metals and Its Associations with Unexplained Recurrent Miscarriage - Yingying Zhang; Xi Yan; Jianhua Tan; Jifan Tan; Chunsheng Liu; Pan Yang; Yanping Xian; Qiong Wang (Toxics, 2023)
Exposure to heavy metals exerts toxic effects on female reproduction and embryo development. This study examined the exposure of patients with unexplained recurrent miscarriage (uRM) to multiple metals and the correlations among exposures to different metals. A total of 275 participants were enrolled, including 43 healthy women without previous miscarriage (the control group) and 232 uRM women (the case group); among these uRM women, 159 had two miscarriages (2M), 42 had three miscarriages (3M) and 31 had four or more miscarriages (≥4M). A total of 22 elements were measured in serum samples via inductively coupled plasma–mass spectrometry. The levels of calcium (104.37 mg/L vs. 92.65/93.02/92.61/92.47 mg/L) and selenium (131.85 µg/L vs. 117.80/118.04/115.88/124.35 µg/L) were higher in the controls than in the total uRM group and the 2M, 3M and ≥4M subgroups. The level of vanadium was significantly lower in the controls than in the total uRM group (0.15 µg/L vs. 0.23 µg/L), and the level of lead was lower in the controls than that in the total uRM group and the 2M, 3M and ≥4M subgroups (0.01 µg/L vs. 0.28/0.18/0.63/0.34 µg/L). After adjusting for age, body mass index and education level, calcium and selenium exposure were consistently negatively associated with miscarriage, while lead exposure was positively associated with miscarriage. In addition, the correlations among exposures to different metals slightly differed between the control and uRM groups. Therefore, changes in some metal elements in the blood might be related to the risk of uRM.